West Nile virus infection in human and animals: potential risks in Malaysia - Nur Ain Najwa Mohd Yuseri,; Nor Yasmin Abd. Rahaman,; Abdul Rahman Omar,; Siti Suri Arshad,; Jalila Abu,; Hussni Omar Mohammed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
West Nile virus (WNV) is a zoonotic RNA virus maintained in enzootic cycles involving mosquito mainly Culex and Aedes spp. as the vector and birds as the reservoir host. WNV is endemic in Africa, Europe and Western Asia. Human infection results in asymptomatic illness such as fever, headache, tiredness, body aches, nausea, vomiting, skin rash, swollen lymph glands and neuroinvasive disease are seen in less than 1% of infected persons. The spectrum of symptoms in animals includes fever, weakness and paralysis of hind limbs, impaired vision, ataxia, head pressing, aimless wandering, seizures, inability to swallow, walking in circles and coma. Based on the previous study in Malaysia, the antibody and nucleic acid against WNV were detected in Orang Asli, captive birds and horses. In this paper, potential risk factors contributing to WNV occurrence are discussed. How the disease or infection is diagnosed and controlled was also discussed.